Retraction: The PI3K/Akt and NF-κB signaling pathways are involved in the protective effects of Lithocarpus polystachyus (sweet tea) on APAP-induced oxidative stress injury in mice. Issue 44 (7th October 2022) - Yang, Jia-yu; Zhong, Yu-te; Hao, Wei-nan; Liu, Xiang-xiang; Shen, Qiong; Li, Yan-fei; Ren, Shen; Wang, Zi; Li, Wei; Zhao, Li-Chun
Abstract : Retraction of 'The PI3K/Akt and NF-κB signaling pathways are involved in the protective effects of Lithocarpus polystachyus (sweet tea) on APAP-induced oxidative stress injury in mice' by Jia-yu Yang et al., RSC Adv., 2020, 10, 18044–18053. ; https://doi.org/10.1039/D0RA00020E .